Effect of Grain Size on the Spall Fracture Behaviour of Pure Copper under Plate‐Impact Loading. (12th March 2015) - Chen, T.; Jiang, Z. X.; Peng, H.; He, H. L.; Wang, L. L.; Wang, Y. G.
Abstract The effects of grain size on the spall response were investigated for high purity copper materials by plate‐impact experiments including real‐time measurements of the free surface velocity profiles as well as post‐impact fractography studies on the soft‐recovered samples. High purity copper plates were cold rolled and heat treated to produce recrystallized samples with average grain sizes of 78, 273 and 400 μm, respectively. The spall strength estimated from the free surface velocity profile is nearly constant with no significant effect on the grain size. However, differences are observed in the acceleration rate of velocity rebound beyond the minima. This may be attributed to the effect of grain size on the growth rate of damage. Metallographic analyses of the fracture surface show that the characteristic feature of the fracture surface clearly depends on the grain size. In the 78‐ and 273‐μm samples, the fracture surfaces are decorated with large, high‐density ductile dimples suggesting that the preferential failure mode is ductile intergranular fracture. In the 400‐μm samples, the fracture surfaces have a rock candy appearance with small, high density brittle dimples as well as large ductile dimples suggesting that the fracture mode is a mix of both brittle intergranular fracture and ductile transgranular fracture.